Manajemen Sumber Daya Manusia (SDM) dan Kewirausahaan - Ramadhani, Aulia; Umagapi, Dara Anindya Putri; Rachman, Tutut Arif; Rahayu, Wening Patmi; Winarno, Agung (Jurnal Ekonomi, Bisnis dan Manajemen, 2025)
Managing human resources and entrepreneurship are two crucial components of any successful organization. Human resources management focuses on recruiting, training, and retaining employees to ensure they can perform their job duties effectively. On the other hand, entrepreneurship involves the creation and development of new business ventures, products, or services. Both areas play a significant role in the overall success and growth of a company. In this paper, we will explore the intersection of human resources management and entrepreneurship, examining how these two disciplines can work together to drive innovation and organizational success. By leveraging the expertise and creativity of both HR professionals and entrepreneurs, companies can cultivate a culture of innovation and adaptability. This collaboration can lead to the development of cutting-edge products and services, as well as the implementation of forward-thinking HR practices that attract and retain top talent. However, integrating HR and entrepreneurship may also present challenges, such as balancing risk-taking with employee well-being and ensuring that organizational goals align with individual aspirations. Despite these obstacles, the potential benefits of combining these disciplines are vast, offering companies a strategic advantage in today's competitive business landscape.